Right to appropriate representation of defendants with intellectual disabilities in criminal proceedings (Ius Novum, 2020)
The subject of this paper is a discussion of selected issues related to ensuring appropriate representation for people with intellectual disabilities against whom criminal proceedings are conducted. The need to grant them additional rights stems from the Commission Recommendation of 27 November 2013 on procedural safeguards for vulnerable persons suspected or accused in criminal proceedings. The text points to problems connected with ensuring in practice the participation of a defence counsel for this category of the accused and with inadequate Polish procedural regulations concerning the obligation to ensure the presence of a legal representative or an appropriate adult during preparatory proceedings and a court hearing. The text also draws attention to the inequality in this respect of the legal situation of the accused and the injured party who require additional support due to, for instance, intellectual development disorders suffered by them.
Keywords: vulnerable person; accused person with intellectual disability; legal representation; appropriate adult